Nursing Students' Perceptions of Just Culture in Nursing Programs: A Multisite Study. Issue 3 (May 2020) - Walker, Danielle; Altmiller, Gerry; Hromadik, Lora; Barkell, Nina; Barker, Nancy; Boyd, Teri; Compton, Michelle; Cook, Pamela; Curia, Marianne; Hays, Deana; Flexner, Randi; Jordan, Janet; et al.
Abstract : Background: While just culture is embraced in the clinical setting, just culture has not been systematically incorporated into nursing education. Purpose: The purpose of this study was to assess prelicensure nursing student perceptions of just culture in academia. Methods: Following a quantitative, descriptive design, the Just Culture Assessment Tool for Nursing Education (JCAT-NE) was used to measure just culture across multiple (N = 15) nursing programs. Results: The majority of JCAT-NE respondents (78%) reported their program has a safety reporting system, 15.4% had involvement in a safety-related event, and 12% submitted an error report. The JCAT-NE mean total score was 127.4 (SD, 23.6), with a statistically significant total score decline as students progressed from the beginning (133.6 [SD, 20.52]) to the middle (129.77 [SD, 23.6]) and end (122.2 [SD, 25.43]) of their programs ( χ 2 [2] = 25.09, P < .001). Conclusions: The results from this study are a call to action for nursing education to emphasize the tenets of just culture, error reporting, and quality improvement. Abstract : Supplemental digital content is available in the text.